Sudden stops in portfolio investment flows to East Asia and Pacific Region. An evidence from Indonesia and Singapore - Broszkiewicz, Magdalena (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The main aim of the article is to conduct the analysis of the different levels of development of Indonesia and Singapore capital markets between 1995 and 2015 and show that in both cases a sudden stop occurs, especially in the period of regional and global financial crises. However, it is possible to see a faster return to stabilization in the developed market, and therefore better opportunities for attracting foreign capital. International capital flows in this article shall be construed as a shift of capital across national borders, recorded in the account balance of payments
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 202-214
Keywords: portfolio investment; sudden stops of international capital flows; capital markets; East Asia and Pacific; inwestycje portfelowe; nagłe zatrzymanie napływu kapitału; rynki kapitałowe; region Azji Wschodniej i Pacyfiku